A case study on Staphylococcus aureus bacteraemia: available treatment options, antibiotic R&D and responsible antibiotic-use strategies. Issue 2 (19th June 2020) - Monnier, Annelie A; Tacconelli, Evelina; Årdal, Christine; Cavaleri, Marco; Gyssens, Inge C
Abstract: Objectives: This case study addresses: (i) antibiotic treatment options for Staphylococcus aureus bacteraemia (SAB), for both empirical and targeted therapy; (ii) the current status of and priorities for the antibiotic pipeline to ensure access of effective antibiotics for SAB; and (iii) strategies for responsible antibiotic use relevant to the clinical management of SAB. Methods: Evidence to address the aims was extracted from the following information sources: (i) EUCAST and CLSI recommendations, summaries of product characteristics (SPCs), antibiotic treatment guidelines and the textbook Kucers' The Use of Antibiotics ; (ii) the www.clinicaltrial.gov database; and (iii) quality indicators for responsible antibiotic use. Results: Current monotherapy treatment options for SAB include only three drug classes (β-lactams, glycopeptides and lipopeptides), of which two also cover MRSA bacteraemia (glycopeptides and lipopeptides). The analysis of the antibiotic pipeline and ongoing clinical trials revealed that several new antibiotics with S. aureus (including MRSA) coverage were developed in the past decade (2009–19). However, none belonged to a new antibiotic class or had superior effectiveness and their added clinical value for SAB remains to be proven. Responsible antibiotic use for the treatment of SAB was illustrated using 11 quality indicators. Conclusions: Awareness of the problem of a limited antibiotic arsenal, together with incentives (e.g. push incentives), is needed to steer the R&D landscape towards the development of novel and effective antibiotics for treating SAB. In the meantime, responsible antibiotic use guided by quality indicators should preserve the effectiveness of currently available antibiotics for treating SAB.